2016
DOI: 10.1080/02656736.2016.1204629
|View full text |Cite
|
Sign up to set email alerts
|

Real-time qualitative MR monitoring of microwave ablation in ex vivo livers

Abstract: The current ex vivo liver model experiment suggests that real-time qualitative MR monitoring of MWA is feasible. Further research using in vivo and human models are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The frequency of RF ablation generators interferes with the MR scanner making imaging during the ablation procedure impossible without the use of additional filters [13,26]. However, microwave ablation generators work at higher frequencies of 915 MHz or 2.45 GHz, which may improve imaging control during an on-going ablation procedure [27].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of RF ablation generators interferes with the MR scanner making imaging during the ablation procedure impossible without the use of additional filters [13,26]. However, microwave ablation generators work at higher frequencies of 915 MHz or 2.45 GHz, which may improve imaging control during an on-going ablation procedure [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our experience when the EMI was present it also tended to increase in intensity towards the end of ablations, as tissue properties changed (potential limitation of our QA testing using saline is that saline's properties remain constant during the MWG activation), occasionally still degrading the dose information. One potential approach to mitigate image quality degradation due to EMI is to interleave the ablation with MRI data acquisition, i.e., only acquiring MRI thermometry images when the microwave is temporarily powered off or in stand-by mode [22]. This approach, however, can potentially compromise the…”
Section: Discussionmentioning
confidence: 99%
“…In our practice MR-guided MWA treatments are performed using a commercially available MRI-configured microwave AveCure system (MedWaves Inc., San Diego, CA) operating at 902-928 MHz, inside a 1.5 T diagnostic horizontal bore scanner (Ingenia, Philips Healthcare, Best, Netherlands). The AveCure system in similar configuration has previously been used in MWA of ex-vivo porcine livers [22]. In that study the MR-monitoring was accomplished using the temperature-related signal changes in T1-weighted images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the latter, however, MRI-suitable materials are needed, and so far, most available devices are not MRI safe. However, if MRI-suitable materials can be used novel studies showed that MRI can accurately display the ablation zones and could also be used as real-time monitoring 27,28 . Still, accuracy of needle placement can be hampered in some MRI systems by the comparably narrow gantry, unless an open MRI system is used 29,30 .…”
Section: Discussionmentioning
confidence: 99%